How do organizations respond to workplace deviance under the influence of organizational citizenship in public universities? - Abbasi, Ali; Cary, John C.; Herjanto, Halimin; Baradari, Fatemeh; Muslim Amin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This paper explores the parallel roles in an organization as it relates to the level of commitment shown by its employees (citizens of the company) and their workplace deviance. The study goes a step deeper to show how this relationship is intertwined with the theory of social exchange. A total of 600 respondents consisted of lecturers and employees from the top five Malaysian public research universities, but only 189 were suitable for statistical analysis. Current research employs a deductive approach and uses nonprobability sampling. SEM-PLS is used to examine the research model and test the mediating effect of organizational citizenship behaviour on the relationship between organizational commitment and workplace deviance. The results reveal what is known to be true between healthy commitment and organizational citizenship as well as the dangers of workplace deviance on that relationship. Despite this positive relationship, workplace deviance does in fact modify organizational commitment in a negative manner. The study’s findings have shown empirically that workplace deviance does influence behaviours and perhaps dampens the relationship between organizational citizenship and its commitment to the organization itself. The outcome of the research data can help future managers, particularly in tertiary education settings, in implementing appropriate organizational mechanisms towards improving organizational citizenship behaviour. In addition, the findings can also provide insights for other public and private universities alike in approaching workplace deviance.